The New Science and Women's Literary Discourse
XVI, 263 p.
Keywords: Looking at literary discourse, including poetry, fiction and non-fiction, diaries, and drama, this collection offers remarkable and fascinating examples of women writers who integrated scientific material in their literary narratives.